The lesson of Physical Education, a way to learn about local sports history - Bárbara Aleida Lam Peralta; Osmani González Hernández; María Hildelisa Gourguet Carbonell (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
The present research was developed in Guane town, a province of Pinar del Río, Cuba, aimed at offering a tool to transmit the knowledge of the local sports history from a developing conception in students through the teaching-learning process of Physical Education based on the teacher's guidance. It is supported on a diagnosis in which insufficiencies lead to a poor treatment of the sport identity from the Physical Education lesson, not taking advantage of the potential that the content that this subject provides, in the framework of the educational teaching process, to provide knowledge to the students on local history, particularly sports. As research scientific methods were used at the theoretical and empirical level: conducting a thorough review and analysis of all those elements related to the subject in question, including publications, archival documents, unpublished materials, manuscripts, articles of magazines and newspapers, available in the province, besides the observation and interviews applied to professors and methodologists of the municipality. As a result, a historical review is presented where the most significant events and elements related to sports development in Guane municipality, which include: main sports results, practiced sporting events, facilities, the most relevant sports personalities, among other elements of interest. The work as a whole contributes to the knowledge of the local history of the municipality, it is moreover, a useful tool for the teacher in the integral formation of the students.